SMALL LYMPHOCYTIC LYMPHOMA PRESENTING WITH CHANGE IN VOICE - DR. P.MELLONIE,; DR. B.O.PARIJATHAM, (International Journal of Pharma and Bio Sciences, 2014)
Non Hodgkins Lymphoma includes all lymphomas except Hodgkins lymphoma.Non Hodgkin’s Lymphoma can be nodal and extranodal. Among the extranodal sites for NHL8, the head and neck region accounts for 10 to 30 % and the waldeyer’s ring is involved in 60 to 70% of such cases. 37 % of Non Hodgkin’s Lymphoma7 that affects the Waldeyer’s ring involves the palatine tonsil and most of them are high grade6 lymphomas.This paper presents a case of 42-year-old male who presented with change in voice and turned out to have Small Lymphocytic Lymphoma1(SLL) in the tonsil.This case is presented for its rarity, as most lymphomas that involve the tonsil are high grade lymphomas like the diffuse large B cell lymphomas. Low-grade lymphomas like SLL are exceptionally rare.